3D Cell Cultures: Nanostructured Superhydrophobic Substrates Trigger the Development of 3D Neuronal Networks (Small 3/2013). Issue 3 (1st February 2013) - Limongi, Tania; Cesca, Fabrizia; Gentile, Francesco; Marotta, Roberto; Ruffilli, Roberta; Barberis, Andrea; Dal Maschio, Marco; Petrini, Enrica Maria; Santoriello, Stefania; Benfenati, Fabio; Di Fabrizio, Enzo
<x xml:space="preserve">Abstract</x> On page 402, E. Di Fabrizio and co‐workers describe the growth of neuron–astrocyte co‐cultures on nanostructured superhydrophobic substrates. The scanning electron microscopy image on the inside cover shows a flat glial cell monolayer (pink) suspended between adjacent nanostructured pillars. Astrocytes adhere with high affinity to both the top and lateral surface of the pillars and provide an excellent support for cocultured neurons, as shown by a large neuron (blue) spreading upon the glial carpet with its multiple neuritic processes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>